Validation of Cytomegalovirus Immune Competence Assays for the Characterization of CD8+ T Cell Responses Posttransplant - Eugene V. Ravkov; Igor Y. Pavlov; Kimberly E. Hanson; Julio C. Delgado (Clinical and Developmental Immunology)
Cytomegalovirus (CMV) infection is one of the most important infectious complications of transplantation. Monitoring CMV-specific CD8 T cell immunity is useful for predicting active CMV infection and for directing targeted antiviral therapy. In this study, we examined four basic parameters for validation of CMV-specific tetramer staining and peptide stimulation assays that cover five most frequent HLA class I alleles. We also examined the potential use of CMV-specific CD8+ T cell numbers and functional and cytolytic responses in two autologous HSCT recipients treated for multiple myeloma. The coefficient of variation (CV %) of the precision within assays was 3.1−24% for HLA-tetramer staining, 2.5−47% for IFN-γ, and 3.4−59.7% for CD107a/b production upon peptide stimulation. The precision between assays was 5−26% for tetramer staining, 4−24% for IFN-γ, and 5−48% for CD107a/b. The limit of detection was 0.1−0.23 cells/μL of blood for tetramer staining, 0−0.23 cell/μL for IFN-γ, and 0.11−0.98 cells/μL for CD107a/b. The assays were linear and specific. The reference interval with 95% confidence level was 0−18 cells/μL for tetramer staining, 0−2 cells/μL for IFN-γ, and 0–3 cells/μL for CD107a/b. Our results provide acceptable measures of test performance for CMV immune competence assays for the characterization of CD8+ T cell responses posttransplant measured in the absolute cell count per μL of blood.